Deformation Analysis of Reinforced Retaining Wall Using Separate Finite Element - Xingli Jia; Jinliang Xu; Yuhai Sun (Discrete Dynamics in Nature and Society)
In order to reveal the main factors affecting the deformation of reinforced soil retaining wall and the influence of various factors on the deformation, the constitutive relation is discretized into four aspects of soil, geogrid, wall panel, and contact surface, and discrete element matrices are, respectively, constructed, with the method of separate finite element. Based on the finite element geotechnical analysis technology platform, the deformation analysis model of reinforced soil retaining wall is established. Taking the modulus of foundation soil as the influencing factor of the foundation soil, taking the geogrid stiffness, length, and spacing as the influencing factors of geogrids, and taking the filling type of limestone, fly ash, and silty clay as the influencing factors of backfill in the wall, the horizontal and vertical deformations of reinforced retaining wall under different factors using the methods of controlling a single variable analysis are calculated. The results show that the increase of elastic modulus of foundation soil will reduce the vertical deformation of the wall but increase the horizontal deformation. The silty clay is not suitable as filler, and lime soil is slightly better than fly ash. The spacing between geogrids is 20 cm ~ 60 cm, which has less effect on wall deformation, but the horizontal deformation rapidly increases after the spacing increases to 80 cm, and other grid performance influencing factors also have the characteristic, where there exists a threshold. The wall will have a greater deformation when the threshold is not reached; a higher indicator of the grid to reduce the deformation of the retaining wall is not obvious after reaching the threshold.